If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 6(x + 4) + -5 Reorder the terms: 7 = 6(4 + x) + -5 7 = (4 * 6 + x * 6) + -5 7 = (24 + 6x) + -5 Reorder the terms: 7 = 24 + -5 + 6x Combine like terms: 24 + -5 = 19 7 = 19 + 6x Solving 7 = 19 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 7 + -6x = 19 + 6x + -6x Combine like terms: 6x + -6x = 0 7 + -6x = 19 + 0 7 + -6x = 19 Add '-7' to each side of the equation. 7 + -7 + -6x = 19 + -7 Combine like terms: 7 + -7 = 0 0 + -6x = 19 + -7 -6x = 19 + -7 Combine like terms: 19 + -7 = 12 -6x = 12 Divide each side by '-6'. x = -2 Simplifying x = -2
| 4(8n+2)= | | 6(x-3)-5=7 | | 6m-10=-30+m | | 4x^2+3x=10 | | -6(u+4)=-4u-40 | | 0.35*(22364+x)=x | | 2(x+5)-8=14 | | 7=6(x+1)-5 | | -3x+6.3=14.4 | | 8w-26=5(w-4) | | -7=-2 | | 7=6x-5 | | -3x+6-3=14.4 | | x-5y=14 | | 7x^2+12+25x=0 | | (y+42)-15=-3 | | 4(n+1)+(n+3)=5(n+1)+2 | | -5(x+8)=-8x-49 | | 6x^2-11=-3 | | 3x-6y=15 | | 6y=4y+18 | | -1.6n+7.9=8.4 | | 4x^2+25x-21=0 | | 3x^3-9x+1=0 | | -14=-6x+4(x-3) | | x+2=2(3x-4) | | 5(x-3)-10= | | 7x+3x+8=-102 | | 5(v+7)-8v=26 | | 10x+1=81 | | 3x-5=13x-105 | | 5(1-n)+3n=3(n-1)-5n |